Development and characterization of 3d-printed bioactive glass-doped scaffolds - ULAĞ, SONGÜL (My University, 2023)
Bone tissue is a complex type of tissue containing various microstructures with high regenerative properties. Depending on the extent of damage to the bone tissue damaged by various diseases and traumas, it may not be possible to completely heal on its own. In such cases, synthetic or natural materials called bone grafts are used instead of the damaged bone tissue, which will provide structural support to the surrounding tissues and provide a suitable environment for cells to attach and multiply. The contribution of bone graft to the treatment process depends on the success of the graft material, micro and macro structure, chemical structure and interaction with the tissues. Materials that are used in bone tissue engineering and have the ability to bond with the natural bone structure are called bioactive materials. Among bioactive materials, bioglasses have a very important place. Bioactive glass material and bone tissue with the right composition can support the tissue during regeneration by forming very strong bonds and can play an active role in the treatment of the tissue by providing the ions needed by the bone cells with the ions such as calcium and silicon in its content. In addition to the material used in bone tissue scaffolds for the growth and proliferation of bone cells, these materials must have the correct morphological properties (eg, surface structure, macro and micro porosity, graft shape size and physical strength). Although bioactive glass materials meet these criteria as a material, they can generally be used as powder additives in bone tissue scaffolds due to their low machinability, fragility, and synthesis methods. In this study, Sol-Gel is used to produce bone tissue scaffolds in the desired shape, size, porosity and morphology by shaping the bioactive glass material synthesized by Sol-Gel method using a 3-dimensional printer during the synthesis process and stabilizing it with additional processes such as curing and sintering. Synthesis parameters and 3- dimensional printing method were optimized to allow sol-gel material to be printed. A new production method was developed in the field of bone tissue engineering with the production of glass material by performing Sol-Gel bioactive glass synthesis and 3D printing together. In the study taken as an example by Valanezhad et al., 2021, bioglass, which was synthesized by the sol-gel method, was produced in gel form and impregnated on a polyurethane sponge, and a scaffold with low mechanical strength was produced. With this study, we aimed to produce scaffolds with high strength, whose morphological properties can be precisely controlled, thanks to the 3-dimensional biowriting technique. Characterisation tests such as FTIR, XRD, SEM and Cell Culture tests were studied on the produced tissue scaffolds. Using the combination ofSol-Gel method and 3D printing technique is a novel method that allows to form bioglass material with specific geometry for optimum material performance in specific applications.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)